Application of molecular techniques in soil microbiology for the identification of bacteria with agricultural potential: a review and bibliometric analysis - Dodino-Gutiérrez, Carlos Andrés; Santiago-Galvis, Juan Manuel; Rabelo-Florez, Roger Alberto; Cubillos-Hinojosa, Juan Guillermo (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2023)
The excessive use of agrochemicals and poor agricultural practices have increased the negative effects on soil and crop biodiversity. In that sense, there is a need to identify potential bacteria by molecular techniques for sustainable agricultural production. The objective of this article was to develop a systematic and bibliometric mapping of the research carried out applying molecular techniques in soil microbiology for the identification of bacteria with agricultural potential. A search for research related to molecular techniques used for the identification of bacteria with agricultural potential was carried out in the Web of Science and Scopus databases, which were classified and analyzed by means of the R studio software. The origin, theoretical reference, bibliometric study and networks on the proposed topic were analyzed from the research obtained. A total of 527 researches related to molecular techniques used for the identification of bacteria with agricultural potential were reported, increasing by 52.75% in the last five years, with an annual growth rate of 17.4%, with India standing out as the country with the highest number of publications, contributing 25% of researches worldwide. Sequencing and PCR are the most common techniques to identify potential microorganisms, being Bacillus, Pseudomonas, Enterobacter and Acinetobacter the most frequent bacterial genera to be identified due to mechanisms used to favor sustainable agricultural production systems.